2014
DOI: 10.1071/sh14017
|View full text |Cite
|
Sign up to set email alerts
|

Social support and depressive symptoms among 'money' boys and general men who have sex with men in Shanghai, China

Abstract: The primary objective was to examine prevalence and correlates of social support and depressive symptoms among male sex workers (known as 'money boys' (MBs)) and general men who have sex with men (MSM) in Shanghai. The Social Provision Scale (SPS), which consists of 24 items, scored out of 4 for social provision, was used to evaluate the functions of social relationships. The score for each item ranges from 1 to 4, with a higher score indicating more social provision. The overall mean SPS score was 68.1 (s.d.=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 20 publications
2
18
2
Order By: Relevance
“…Further, their chances of engaging in risky sexual behavior and reporting depression decrease. Similar findings are reported in Australia and China, where studies have shown that enriched social support has a negative association with depression among MSM [14]- [16]. Recognizing the role of community groups and community based organizations play in HIV prevention, "Pehchan" program is a rare example of a community systems strengthening program funded by Global Fund working at a national scale from 2010 in India.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Further, their chances of engaging in risky sexual behavior and reporting depression decrease. Similar findings are reported in Australia and China, where studies have shown that enriched social support has a negative association with depression among MSM [14]- [16]. Recognizing the role of community groups and community based organizations play in HIV prevention, "Pehchan" program is a rare example of a community systems strengthening program funded by Global Fund working at a national scale from 2010 in India.…”
Section: Discussionsupporting
confidence: 58%
“…In a study in Shanghai, China, lack of social support was found to be a factor influencing high rates of depression among MSM [16]. Poor mental health is shown to increase high-risk behaviors in low-and middle-income countries [17]- [20].…”
Section: Introductionmentioning
confidence: 99%
“…More than techniques for prevention of HIV/AIDS or other sexually transmitted infections, their answers reflected a desire for ways to exist with dignity and support, ways to negotiate their gay self identity in a society and world that currently discriminates against them cruelly. To date, silence on such issues has compounded stress, and led to mental health issues not limited to depression and suicide[18,72]. …”
Section: Discussionmentioning
confidence: 99%
“…Previous literature has also indicated that the prevalent stigma and discrimination against homosexuals and the resulting associations with depression can negatively influence quality of life and ability to make healthy decisions, including decisions regarding HIV preventive behaviors or initiation and adherence to HIV treatment [ 23 27 ]. MSM who reported a relative lack of social support and engaged in risky behaviors were more likely to have psychological problems [ 20 , 28 ]. Owing to the substantial mental health implications, more attention should be paid to the psychosocial health problems among the MSM population.…”
Section: Introductionmentioning
confidence: 99%